How to be a design academic : from learning to leading - Blackler, Alethea; Miller, Evonne (Boca Raton, FL : CRC Press, 2021)
"This book is about how to be a design academic. In another words, how to manage the various challenges, requirements, and processes that come with both the everyday and extra-ordinary parts of an academic role in design fields (from architecture, urban design, interior design and landscape architecture, to fashion, industrial, interaction and graphic design). The book is organised in two parts - Part 1, Starting out and Part 2, Becoming a Leader. It includes real-life experiences of actual academics and offers a wide range of experiences of authors from early career researchers to full professors and heads of schools. It contains all aspects of academic life, including the highs and lows of teaching, research, leadership, and managing your working life and your career. This book is perfect for academics, aspiring academics, and research students in a wide range of design fields"--
Crafting your unique career path -- Becoming a successful design researcher -- Becoming a successful design educator -- Leading yourself -- Leading others -- Leading a group or school.
OCLC-licensed vendor bibliographic record.
Keywords: Design -- Study and teaching (Higher); College teachers -- Vocational guidance; TECHNOLOGY / Engineering / Industrial; BUSINESS & ECONOMICS / Quality Control